A detailed lake-level reconstruction shows evidence for two abrupt lake drawdowns in the late-stage history of the eastern Lake Agassiz-Ojibway basin. (15th June 2020) - Godbout, Pierre-Marc; Roy, Martin; Veillette, Jean J.
Abstract: Glacial Lake Ojibway occupied large areas in northeastern Ontario and northwestern Quebec during the last deglaciation. Paleogeographic reconstructions depict Lake Ojibway and Lake Agassiz sharing a common water plane shortly before the final drainage of this lake ∼8200 years ago. However, the pre-drainage surface elevation and extent of this large coalesced lake is based on scattered raised shorelines in the Ojibway basin and poorly constrained geomorphological considerations, which convey large uncertainties in lake-level reconstructions and the attendant meltwater volume estimates used to assess the impact of this freshwater discharge. Here, we address this issue by using 3098 elevation measurements of shorelines mapped on a LiDAR digital terrain model covering a key area in the Ojibway basin. Our reconstruction is based on a GIS model integrating the paleotopography, which reinforces correlation of shorelines and the identification of lake levels. The spatial distribution of shoreline-elevation data points shows well-defined clusters of shorelines aligned on distinct elevation ranges that delineate three widespread lake levels, which are separated by two intervals with atypically low number of shorelines reflecting abrupt lake drawdowns. This reconstruction considerably refines the sequence in the eastern (Ojibway) basin and shows evidence for a two-step drainage of Lake Agassiz-Ojibway. The results provide constraints on the magnitude of the lake-level drops and indicate that the pre-drainage surface-elevation of Lake Agassiz-Ojibway of earlier reconstructions was likely overestimated. Accordingly, the configuration and structure of this lake stage should be re-evaluated. To that effect, the new shoreline record provides an important framework for assessing late-stage changes in lake levels across the Agassiz-Ojibway basin, which is a critical step towards the production of realistic models depicting the drainage of this large lake. Highlights: We report 3098 elevation measurements of raised shorelines mapped on a LiDAR-derived DTM. The lake-level history of Lake Ojibway is reconstructed through a GIS-based approach. We identify three widespread lake levels separated by two major lake drawdowns. The reconstruction shows evidence for a two-step drainage of Lake Agassiz-Ojibway. Former meltwater volume estimates of drainage events should be re-evaluated.